Analysis on the Performance of a Prototype of Thermoelectric based Power Generation System - Elghool, Ali; F., Basrawi; Hassan, Ibrahim; Daing Mohamad Nafiz, Daing Idris; Khairul, Habib; Mohd Hazwan, Yusof (EDP Sciences, 2018)
There are needs on electricity but people cannot get electricity including when doing outdoor activities at isolated areas, selling goods in night market and during disaster such as flood and earthquake. People need electricity especially for charging communication gadgets and lighting. Thus, the objective of this study is to develope and test the performance of a small prototype of thermoelectric generator (TEG) based power generation system. The TEG based power generation system developed consists of heat collector, thermoelectric generator, heat pipe and fin based heat sink, and DC-DC converter. The heat collector was designed to ensure the suitable temperature for the TEG which is should not exceed 320 0C on the hot side. Heat pipes was used to increase the power output by lowering or maintaining the temperature at cold side, to ensure large temperature difference is obtained. The prototype was tested and data of temperature, voltage and current were collected. A cell phone was used during the test as a load to the system. All the data were recorded by using temperature data recorder, power meter and multimeter. It was found that the highest maximum power output was 7.7 watt at the temperature difference of 138oC. The output is sufficient to charge the cell phone and it is also possible to light an LED bulb. However, it did not achieve the maximum output of 43 W. This is a results of limitation of maximum electrical load (only one cell phone was used) and the limitation of the performance of the prototype. Thus, although the prototype is succesfully generate enough power to charge a cell phone, but improvement in heat sink design, and adding more electrical load are needed to get better results.